Immunization with a DNA vaccine cocktail encoding TgPF, TgROP16, TgROP18, TgMIC6, and TgCDPK3 genes protects mice against chronic toxoplasmosis - Zhang, Nian-Zhang; Gao, Qi; Wang, Meng; Elsheikha, Hany M.; Wang, Bo; Wang, Jin-Lei; Zhang, Fu-Kai; Hu, Ling-Ying; Zhu, Xing-Quan (Frontiers Media, 2018)
Toxoplasmosis is a zoonotic disease caused by the intracellular protozoan Toxoplasma gondii; and a major source of infection in humans is via ingestion of T. gondii tissue cysts. Ultimately, the goal of anti-toxoplasmosis vaccines is to elicit a sustainable immune response, capable of preventing formation of the parasite tissue cysts—or, at least, to restrain its growth. In this study, we formulated a cocktail DNA vaccine and investigated its immunologic efficacy as a protection against the establishment of T. gondii cysts in the mouse brain. This multicomponent DNA vaccine, encoded the TgPF, TgROP16, TgROP18, TgMIC6, and TgCDPK3 genes, which play key roles in the pathogenesis of T. gondii infection. Results showed that mice immunized via intramuscular injection three times, at 2-week intervals with this multicomponent DNA vaccine, mounted a strong humoral and cellular immune response, indicated by significantly high levels of total IgG, CD4+ and CD8+ T lymphocytes, and antigen-specific lymphocyte proliferation when compared with non-immunized mice. Immunization also induced a mixed Th1/Th2 response, with a slightly elevated IgG2a to IgG1 ratio. The increased production of proinflammatory cytokines gamma-interferon, interleukin-2, and interleukin-12 (p < 0.0001) correlated with increased expression of p65/RelA and T-bet genes of the NF-κB pathway. However, no significant difference was detected in level of interleukin-4 (p > 0.05). The number of brain cysts in immunized mice was significantly less than those in non-immunized mice (643.33 ± 89.63 versus 3,244.33 ± 96.42, p < 0.0001), resulting in an 80.22% reduction in the parasite cyst burden. These findings indicate that a multicomponent DNA vaccine, encoding TgPF, TgROP16, TgROP18, TgMIC6, and TgCDPK3 genes, shows promise as an immunization strategy against chronic toxoplasmosis in mice, and calls for a further evaluation in food-producing animals.